A rolled cookie machine. - Shamsuddin, Rosnah; Hamzah, Azman; Pua, Ming Yee; Endon, Johari (2011)
The present invention generally relates to a machine for preparing a rolled jam tart. The present invention comprises of mechanisms for compressing the dough and the jam, and filing the jam inside the rolled compressed dough. The mechanism involved is co-extrusion mechanism. The present invention also aided with a sensor for cutting the tart automatically and uniformly.